Experimental Measurement of Forward Scattering from Very Rough Sand Ripples in a Water Tank - Liang Wang; Gaokun Yu; Minshuai Liang; Yun Ren; Linhui Peng (Remote Sensing, 2022)
High order Bragg scattering from sand ripples is investigated by a tank experiment, where the artificially produced sand ripples have a spatial period of 0.2 m and ripple height of 5 cm. Bragg scattering has been measured at three frequencies 22 kHz, 24.57 kHz, and 27 kHz and three incident grazing angles <semantics>20∘</semantics>, <semantics>30∘</semantics>, <semantics>40∘</semantics> by a method based on the conventional beamforming using two horizontal receiving arrays. It is illustrated that high order Bragg scatterings can be observed, and the corresponding scattered grazing angles agree with the theoretical prediction. Owing to the ripple height being on the order of wavelength, it is found that the distribution of forward scattering amplitude is different from the distribution for sand ripples of small height, i.e., the diffuseness of scattering amplitude is increased with the ripple height.